(untitled) (Indian Journal of Public Health Research & Development, 2020)
India has one-fifth of its population in its adolescence who would become forthcoming productive force. They are at this vital stage of their life and face different scenarios needing for use of their individual skills to manage and cope up with. So this study was undertaken to assess the life skills. Methodology: A cross sectional study using semi-structured questionnaire with the Life skills assessment scale developed by the researchers of Rajiv Gandhi Institute of Youth & Development was conducted. After taking necessary assent from the students, the few demographic data collected was tabulated and analyzed using MS Excel sheet. ANOVA was applied to find the association and parental influence upon the students’ life skills. Results: The findings revealed that boys slightly more than girls across different classes. Mother’s educational status was observed to be on the higher side compared to father’s education. Students scored highest on Critical thinking skills and lowest on Coping with Stress skill. Across individual life skills, girls fared significantly better than boys with the skill of coping with stress & emotions; in the self awareness and decision making capacities, the scores showed slight downward trend in acquisition of skill across different years of schooling.